Proposed Machine Maintenance Management To Reduce Breakdown In Kacang Atom Production Process PT. XYZ With Preventive Maintenance Method - Yusril Ananda Ainun Huda; Pramudi Arsiwi (OPSI, 2022)
PT. XYZ is engaged in the production of snacks. This company makes products from raw materials to finished products. In the packaging section using a machine called CingFong, the problem that often occurs in the packaging section is that there is often a buildup of production materials due to waiting for machines that have not finished maintenance so that it can reduce the productivity of this factory. Overall the method used is Preventive Maintenance by looking for Mean Time To Failure (MTTF) to identify critical components in Cingfong engine parts. From the data processing that has been done, it is known that the Clutch, Blade and Emergency Stop are components that fall into the category of critical components with a total Cumulative Downtime of 70.3%.